Inhibition of Nur77 expression and translocation by compound B6 reduces ER stress and alleviates cigarette smoke-induced inflammation and injury in bronchial epithelial cells - Chang, Chenli; He, Fengming; Ao, Mingtao; Chen, Jun; Yu, Tao; Li, Weiyu; Li, Baicun; Fang, Meijuan; Yang, Ting (Frontiers in Pharmacology, 2023)
Chronic obstructive pulmonary disease (COPD) is a leading cause of death worldwide with inflammation and injury in airway epithelial cells. However, few treatment options effectively reduce severity. We previously found that Nur77 is involved in lipopolysaccharide-induced inflammation and injury of lung tissue. Here, we established an in vitro model of COPD-related inflammation and injury in 16-HBE cells induced by cigarette smoke extract (CSE). In these cells, Nur77 expression and localization to the endoplasmic reticulum (ER) increased following CSE treatment, as did ER stress marker (BIP, ATF4, CHOP) expression, inflammatory cytokine expression, and apoptosis. The flavonoid derivative, named B6, which was shown to be a modulator of Nur77 in previous screen, molecular dynamics simulation revealed that B6 binds strongly to Nur77 through hydrogen bonding and hydrophobic interactions. Treating CSE-stimulated 16-HBE cells with B6 resulted in a reduction of both inflammatory cytokine expression and secretion, as well as attenuated apoptosis. Furthermore, B6 treatment resulted in a decrease in Nur77 expression and translocation to the ER, which was accompanied by a concentration-dependent reduction in the expression of ER stress markers. Meanwhile, B6 played a similar role in CSE-treated BEAS-2B cells. These combined effects suggest that B6 could inhibit inflammation and apoptosis in airway epithelial cells after cigarette smoke stimulation, and support its further development as a candidate intervention for treating COPD-related airway inflammation.